2019
DOI: 10.1007/s42452-019-0285-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of medium on structure, morphology and electrochemical properties of polydiphenylamine/vanadium pentoxide composite

Abstract: A facile, one-pot oxidative polymerization approach was used to synthesize polydiphenylamine (PDPA) and polydiphenylamine/vanadium pentoxide (PDPA/V 2 O 5 ) composite using APS as an oxidizing agent. The reactions were carried out in two different reaction media (i.e. aqueous and acidic). The influence of these two mediums on molecular structure, morphology and thermal stability was investigated using FTIR spectroscopy, X-ray diffraction, SEM-EDS and thermogravimetric analysis. The temperature dependent electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Conjugated polymers (CPs) are a particular category of macromolecules with highly polar structure and conjugated backbone, which are gaining more academic interest as the dielectric materials. The CPs have comparatively higher dielectric constant than that of common thermoplastic or thermosetting polymers owing to their highly polarizable conjugated backbone [32][33][34][35]. By using CPs as the polymer matrix for dispersing nanomaterials, the dielectric properties of the individual components can be integrated effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugated polymers (CPs) are a particular category of macromolecules with highly polar structure and conjugated backbone, which are gaining more academic interest as the dielectric materials. The CPs have comparatively higher dielectric constant than that of common thermoplastic or thermosetting polymers owing to their highly polarizable conjugated backbone [32][33][34][35]. By using CPs as the polymer matrix for dispersing nanomaterials, the dielectric properties of the individual components can be integrated effectively.…”
Section: Introductionmentioning
confidence: 99%
“…The third degradation, at around 558 C corresponds to the degradation of the remaining polymer backbone. 6,24,36 The TGA and DTG thermograms of PDPA/ZnO nanocomposites show similar behavior to that of PDPA with a difference in degradation temperatures and mass loss. All nanocomposites exhibit a slower thermal degradation rate than the parent polymer.…”
Section: Tg Analysismentioning
confidence: 84%
“…This corresponds to the second degradation step (354°C) with a weight loss of 40%. The third degradation, at around 558°C corresponds to the degradation of the remaining polymer backbone 6,24,36 …”
Section: Resultsmentioning
confidence: 99%
“…24,25 Figure 1B represents the polymer modified pencil graphite electrode and it has been understood that the exterior of the flake like structures of the unmodified pencil graphite has been deposited with granular shaped PDPA formed due to the electropolymerization of DPA monomer. 26 The images indicated that the bare PGE has undergone a surface modification process.…”
Section: Resultsmentioning
confidence: 99%